Kepercayaan Kerahasiaan Data Diri Masyarakat Pada Pelayanan Telemedis: Path Analysis Model - Rusdi, Achmad Jaelani; Prisusanti, Retno Dewi; Ikawati, Fita Rusdian; Oktoriani, Ervita Nindy (Politeknik Negeri Jember, 2024)
Online health consultations via telemedicine, conducted through websites or digital platforms, have become a trend with the advancement of communication technology. However, data privacy is a major concern, especially when it involves patients' personal health information. This study analyzes the factors influencing public trust in telemedicine services. The aim is to examine the impact of economic, educational, environmental, usefulness, ease of use, and information quality factors on public trust in telemedicine. The research method involves path analysis using a quantitative approach, followed by qualitative analysis. The study involved 90 participants, with a 2:1 ratio between the user group and the control group. The results indicate a significant influence of economic status, education level, environment, system ease of use, and information quality on public trust in data privacy within telemedicine, with a total trust score reaching +0.545. These findings underscore the need for the public, as telemedicine users, to be more cautious about the security and confidentiality of their personal data. Additionally, service providers must make efforts to ensure patient data security and privacy, while establishing clear terms in every privacy policy and providing legal guarantees regarding data protection.